MANAJEMEN SARANA DAN PRASARANA DALAM MENDUKUNG EFEKTIVITAS PEMBELAJARAN DI SEKOLAH MENENGAH - Ate Jamaludin Mubarok; Ani kania; Imas Nanan Nuraeni; A.D Rima Widianingsih; Ikka Kartika Abbas Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of facilities and infrastructure management in supporting learning effectiveness at MTs AL Jawahir, Soreang District, Bandung Regency. Educational facilities and infrastructure are key factors influencing the quality of the teaching and learning process. This study uses a qualitative descriptive approach with data collection methods through observation, interviews, and documentation studies. The results show that the management of facilities and infrastructure at MTs AL Jawahir has been implemented quite well, covering planning, procurement, maintenance, and evaluation. However, there are still some obstacles, such as budget limitations and a lack of awareness about the importance of maintaining facilities and infrastructure. The effectiveness of learning at this school is influenced by the availability and condition of adequate facilities and infrastructure, as well as optimal management. The implications of this research include the need to increase budget allocation for the procurement and maintenance of facilities and infrastructure, as well as training for educators and staff in school asset management. Thus, learning effectiveness can be significantly improved.